2010
DOI: 10.1007/s00403-010-1047-2
|View full text |Cite
|
Sign up to set email alerts
|

One novel homozygous mutation of SLC39A4 gene in a Chinese patient with acrodermatitis enteropathica

Abstract: Acrodermatitis enteropathica, a rare autosomal recessive disease, manifests as periorificial and symmetrical acral dermatitis, alopecia, and diarrhea due to insufficient zinc uptake by the intestine. Recent research revealed that mutations in the SLC39A4 gene are responsible for acrodermatitis enteropathica. This gene encodes one member of a human zinc transporter-like protein, also known as ZIP4. We detected one novel homozygous mutation c.1115T > G in the human SLC39A4 gene in one Chinese patient, which lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We observed that the Leu372Val polymorphism affects a highly conserved amino acid (Figure 4) and that the same codon position has been altered in acrodermatitis patients carrying missense mutations Leu372Arg [32] and Leu372Pro [8]. Moreover, both PolyPhen [33] and SIFT [34] algorithms predict functional effects for the Leu372Val substitution (see Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…We observed that the Leu372Val polymorphism affects a highly conserved amino acid (Figure 4) and that the same codon position has been altered in acrodermatitis patients carrying missense mutations Leu372Arg [32] and Leu372Pro [8]. Moreover, both PolyPhen [33] and SIFT [34] algorithms predict functional effects for the Leu372Val substitution (see Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…Although the counterpart of G526R in mZIP4 appeared to be normal in cell surface expression and glycosylation ( 15 ), the substantially reduced activity may be caused by the disrupted interaction between G526 on TM5 and the highly conserved F519 on TM4. Remarkably, L372, which is topologically equivalent to M99 facing the binuclear metal center in BbZIP, is replaced by either a proline ( 16 ) or an arginine ( 17 ) in the AE patients. The proline substitution of the same residue in mZIP4 resulted in protein folding defects ( 15 ), probably due to an imposed kink on TM2.…”
Section: Resultsmentioning
confidence: 99%
“…It is quite unexpected that a binuclear metal center is observed in the transport pathway of BbZIP. Binuclear metal centers are known for their catalytic roles in enzymes ( 16 , 17 ), including membrane enzymes ( 21 , 22 ), but it has not been observed within the transport pathway for any known carriers. The distinct coordination environment and markedly different exchangeability suggest that the roles of M1 and M2 are asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 29 mutations have been reported so far: 15 missense, 3 nonsense, 3 splice site and 8 frameshift mutations. [2][3][4][5][6] Among seven other variants of uncertain pathogenicity also reported, 2 three ones, including two missense and a splice site variant, can be considered likely deleterious. No hotspot mutation region is observed, because alterations are evenly distributed all along the 12 exons.…”
Section: Mutational Spectrummentioning
confidence: 99%